Reliability and Validity of the Persian Version of Distress Tolerance Scale - Ali Reza Azizi (Iranian Journal of Psychiatry, 2010)
"nObjectives: This study aims to assess the validity and reliability of the  Persian version of  Simons and Gaher `s Distress Tolerance scale(DTS) by administering it  to nicotine dependent students of Tehran University. "nMethod:In a descriptive cross-sectional study, 317 nicotine dependent students of  Tehran  University who were selected ,using  available sampling method, completed DTS, Coping with Stress- Revised(CS-R), Positive and Negative Affect Scales(PANAS) and Fagerstrom Test  for Nicotine Dependence(FTND).  Data were analyzed using descriptive statistic methods and correlation coefficient. "nResults: The alpha coefficients for Tolerance, Absorption, Appraisal and Regulation subscales were 0.75, 0.77, 0.70 and 0.75, respectively. The test-retest correlation coefficients with two months interval for Tolerance, Absorption, Appraisal  and Regulation subscales and the total scale were 0.71, 0.69, 0.77, 0,73 and 0.79, respectively; all of which were statistically significant (p<0.001). The correlation coefficient of  DTS with problem-focused, emotional-focused, less useful and insufficient coping with stress were found to be:  0.213, -0.278, -0.337 and -0.196.  In addition, the correlation coefficient of  DTS with positive emotion, negative emotion and smoking-dependency were 0.543, -0.224 and -0.653 which were also significant(p<0.05). "nConclusion: the DTS is valid and reliable and suitable to use for assessing distress tolerance.